FAMOTIDINE IN ACUTE DUODENAL ULCER - Manan, Alamzeb (Journal of Ayub Medical College Abbottabad, 1991)
ABSTRACT This is an 8-week open study in which the effect and tolerance of Famotidine, in a dose of 40 mg nocte was tried for the treatment of duodenal ulcer in 22 patients. Assessment was made clinically, biochemically and endoscopically. The healing rate at the end of 8 weeks was 95.45%. The drug was well tolerated with no significant side effect. In conclusion, Famotidine is an effective and safe Duodenal ulcer healing drug, which is well tolerated and has minimal side effects